Factors Relating to Caregivers' Preference for Advance Care Planning of Patients in Japan: A Cross-Sectional Study. (August 2019) - Shaku, Fumio; Tsutsumi, Madoka; Nakamura, Asumi; Takagi, Hiroshi; Otsuka, Takahiro; Maruoka, Shuichiro
Objectives: The aim of this study was to examine the preferences of home caregivers on patient advance care planning (ACP), including life-sustaining treatment (LST) and the factors relating to these preferences. Background: Personalized ACP aims to respect the autonomy and choices of terminally ill patients regarding end-of-life care. However, there have been cases wherein doctors must instead discuss ACP with surrogates (including caregivers) for various reasons such as dementia, intractable neurologic diseases, and cerebrovascular accident. Methods: In this cross-sectional study, self-written questionnaires (filled by individuals themselves) were distributed to 506 in-home caregivers in 6 Japanese prefectures; the questionnaires contained items on caregiver and patient demographics, number of people living together in a caregiver's home (aside from patients), care duration, comprehension level of doctors' explanations regarding their patient's condition, patient diseases, whether caregivers have or have not told patients about their disease, level of nursing care, and caregiver LST preference (preferred or not preferred). The questionnaire package also contained the Burden Index of Caregiver-11, Patient Health Questionnaire-9, and Short Form-8 Health Survey. Results: Valid responses were obtained from 309 caregivers. More than half of them were not sure of their patient's LST preference. Sex, number of people living together in a care home, comprehension level of doctors' explanations, and care duration were found to be the significant factors relating to caregivers' LST preference ( P < .05). Conclusion: Health providers should be cognizant of the background factors relating to caregiver ACP preference when deciding on LST for terminal patients.